Persistent Entrepreneurial Success Through Hobbies in the Era of the Covid-19 Pandemic - Aini, Sofia Nurul (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to examine hobbies that can make someone a persistently successful entrepreneur during the Covid-19 pandemic. This research uses qualitative methods with data collection techniques carried out by interviews with sources. The results of this research show that hobbies can become careers and entrepreneurship. If someone is able to seize opportunities and develop their hobbies, coupled with an entrepreneurial spirit, this will lead to becoming a successful entrepreneur.